Red-to-black electrochromism of 4,9-dihydro-s-indaceno[1,2-b:5,6-b’]dithiophene-embedded conjugated polymers - Cho, Ching Mui (2016)
A series of 4,9-dihydro-s-indaceno[1,2-b:5,6-b′]dithiophene-based conjugated polymers with 3,4-bis(dodecyloxy)thiophene, 3,3-bis((dodecyloxy)methyl)-3,4-dihydro-2H-thieno[3,4-b] [1, 4] dioxepine and 3,4-ethylenedioxythiophene as co-monomers were synthesized via Stille coupling reaction in more than 50 % yields. These polymers possess relatively high number-average molecular weights of 14,900–21,000 g mol−1 and exhibit good solubility in common organic solvents. The physical and electrochemical properties of these polymers were studied, and the polymers showed optical bandgap between 2.04 and 2.08 eV. Electrochromic devices showed a rare and reversible colour change between dark red at neutral state and black at oxidized state with optical switching contrast ratios of up to 50 % at λmax and 90 % at 1500 nm in the visible and NIR regions, respectively.